Metabolomics Profiling Revealed Double-Edged Metabolic Effects of Functionalized Wheat Bran in Mouse. (7th June 2021) - Ma, Yiwei; Lu, Yuwei; Petrofsky, Keith; Ruan, Roger; Chen, Chi
Abstract: Objectives: Wheat bran is rich in bioactive components, mainly dietary fiber, micronutrients, and phytochemical contents. However, the health-promoting effects of wheat bran is restricted by the high-degree crosslinking of dietary fiber and low bioavailability of phytochemicals. The present study aims to improve the functions of wheat bran by increasing the levels of soluble fiber and free ferulic acid from optimized processing to examine the metabolic effects of consuming functionalized wheat bran (FWB) in mice. Methods: Control wheat bran (CWB) was processed by an optimized combination of milling, high pressure pulverization, and alkali treatment, leading to dramatic increases of soluble fiber and free ferulic acid. Three groups of male mice were fed the control AIN93G diet, and two modified AIN93G diets containing 10% of CWB and 10% FWB, respectively, for 7 days. The effects of CWB and FWB on the mouse metabolome were determined through the LC-MS based metabolomics analysis of feces, liver, serum, and urine samples. Results: The processing dramatically improved the function-associated physicochemical properties of wheat bran, including the increases of soluble fiber content and viscosity by milling and high-pressure pulverization and the elevation of free ferulic acid by alkali treatment. FWB feeding elevated microbial SCFAs production, promoted the excretion of bile acids and cholesterol in feces, modified the lipidome in the liver, decreased triacylglycerols and cholesterol in serum, and increased the levels of ferulic acid and microbial metabolites in urine. On the other hand, FWB feeding resulted in the increases of free amino acids in feces and the decreases of essential amino acids, choline and its metabolites in the liver. Conclusions: The optimized processing dramatically increased the soluble fiber and free ferulic acid contents of wheat bran, resulting in improved hypocholesterolemic and antioxidant functions of FWB. However, the bioavailability of nutrients, including essential amino acids and choline, and the homeostasis of lipidome could be negatively affected by FWB diet. These double-edged metabolic effects warrant further investigations on how to achieve the balance between the functionalization of bioactive components and the disruption of nutrient bioavailability in wheat bran processing. Funding Sources: NIFA project MIN-18–125.